Perpetuating gender hierarchy in Indonesia through language: A deconstructive study on the online Kamus Besar Bahasa Indonesia - Ahmad Sirulhaq; Indra Listyo; Maria Adriani; Siti Aisyiyah (Indonesian Journal of Applied Linguistics, 2023)
Gender relations in Indonesian social practices tend to marginalize women, as manifested in various methods and instruments. One of them is the use of language in Kamus Besar Bahasa IndonesiaÂ (online KBBI), an Indonesian dictionary compiled by the Indonesian government. The dictionary is the primary standard and official reference for lemmas, meanings, and examples of sentences. This study aims to analyze the unequal relations between men and women reflected in linguistic units in the online KBBI and uncover their hidden meanings. Data was collected by searching, reading, and recording (documenting) the gender-related lemmas (words), definitions of lemmas, and examples of their use in sentences in the online KBBI from 7 May to 5 June 2022, and applying Derridaâ€™s deconstruction approach to the words and their related features, with its main principles including (1) determining the meanings that are not determined (undecidable), (2) dismantling the ideology of the text (binary logic), (3) reversing the metaphysical hierarchy and neutralize it, and (4) disseminating the meaning. This study found a metaphysical hierarchy between women and men in binary concepts, including domestic-public hierarchy, passive object-active subject hierarchy, and negative-positive hierarchy for women and men regarding lemmas, meanings, and examples of sentences in the online KBBI. These findings suggest that KBBI tends to perpetuate unequal metaphysical hierarchies between women and men in Indonesia. This article is expected to contribute to language awareness and attitudes in Indonesia in addition to improving the online KBBI in terms of its language use.